O supervisor escolar no contexto de formação contínua: repensando o trabalho com leitura e escrita - Costa, Rosângela de Almeida (2011)
This project is about Aplicated Linguistics, following Liberali (2006) in which language organization provides the researching tools to understand and transform didactic concepts and practices, according with historical, politic and social questions. The goal is to analyze the work of the School Supervisor at the pedagogic coordination intending to the comprehension of the reading and writing skills in the public school. It s based on the Social-Historical-Cultural Theory, following Vygostsky (1930/1999, 1930/2000, 1931/1995, 1987, 1934/2001), Leontiev (1977), Bakhtin/ Volochinov (1929/1999) and the Magalhães (2010) discussions of critical collaboration. The research has been done in a public school in the periphery of São Paulo City. The production is composed by audio and video files of interviews and questionnaires. The analysis has been conducted intending to understand the context of lexical and theme organization and the production of new meanings of writing and reading skills